Clinical and autoimmune features of a patient with autism spectrum disorder seropositive for anti—NMDA-receptor autoantibody. Issue 1 (31st March 2017) - Gréa, Hélène; Scheid, Isabelle; Gaman, Alexandru; Rogemond, Véronique; Gillet, Sandy; Honnorat, Jérôme; Bolognani, Federico; Czech, Christian; Bouquet, Céline; Toledano, Elie; Bouvard, Manuel; Delorme, Richard; et al.
Abstract : Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by dysfunctions in social interactions resulting from a complex interplay between immunogenetic and environmental risk factors. Autoimmunity has been proposed as a major etiological component of ASD. Whether specific autoantibodies directed against brain targets are involved in ASD remains an open question. Here, we identified within a cohort an ASD patient with multiple circulating autoantibodies, including the well-characterized one against glutamate NMDA receptor (NMDAR-Ab). The patient exhibited alexithymia and previously suffered from two major depressive episodes without psychotic symptoms. Using a single molecule-based imaging approach, we demonstrate that neither NMDAR-Ab type G immunoglobulin purified from the ASD patient serum, nor that from a seropositive healthy subject, disorganize membrane NMDAR complexes at synapses. These findings suggest that the autistic patient NMDAR-Abs do not play a direct role in the etiology of ASD and that other autoantibodies directed against neuronal targets should be investigated.